Resolution of Enantiomers of (RS)-Baclofen by Ligand-Exchange Thin-Layer Chromatography - Singh, Manisha (J Chromatogr Sci, 2016)
A new chromatographic method has been developed for direct enantioresolution of (RS)-baclofen by ligand-exchange thin-layer chromatography (TLC) adopting two different approaches; (A) TLC plates were prepared by mixing the ligand exchange reagents (LER) with silica gel slurry and the chromatograms were developed with different achiral solvents or solvents having no chiral additive, and (B) the LER consisting of Cu(II)–l-amino acid complex was used as chiral mobile phase additive and the plain plates of silica gel having no chiral selector were used. Cu(II) acetate and four l-amino acids (namely, l-tryptophan, l-histidine, l-proline and l-phenylalanine) were used for the preparation of LERs. Spots were located by the use of iodine vapor. Effect of temperature and the mole ratio of Cu(II)-to-amino acid on enantioresolution were also studied. The results for the two methods have been compared, and the issue of involvement of the Cu(II) cation for the best performance of the two methods has been discussed with respect to the same mobile phase. l-Trp proved to be a good ligand using a common mobile phase in each case.